Flexible dynamic analysis of an offshore wind turbine installed on a floating spar platform - Xiangqian Zhu; Wan-Suk Yoo (Advances in Mechanical Engineering, 2016)
Flexible dynamic analysis is a critical process in designing offshore wind turbines that are composed of several huge components. This process was implemented with a hybrid method of finite element multibody system using commercial software in this article. Based on this method, the tower and blades were modeled as flexible components using three-dimensional solid elements. The effect of flexible deformation of the tower and blades on the global motions of the floating wind turbine was investigated by comparing the simulation results from the flexible body modeling with those from the rigid body modeling. The tower, blades, and spar platform were divided into sections according to the geometry configuration of the 5-MW OC3-Hywind floating wind turbine. The time- and position-dependent loads, coming from the wind, wave, and mooring system, were expressed approximately with respect to the divided sections. The relationships between the global motions and the external loads were studied, which indicated that the wind loads had dominant influences on the translational motions and the rotational motions were mainly generated by the propagating waves.